The shape of water - Toro, Guillermo del, 1964-; Kraus, Daniel, 1975- (New York : Feiwel & Friends, 2018)
In an otherworldly story set against the backdrop of Cold War-era America, an amphibious man is discovered in the Amazon--and subsequently finds love within the human race.
Keywords: Magic realism (Literature); Fantasy fiction; Historical fiction; Movie novels; Romance fiction; Historical fiction; Fantasy fiction